Analysis of Service Quality on User Satisfaction Using the E-Servqual, IPA and CSI Methods - Trivani, Ovie Julian (INOVTEK Polbeng - Seri Informatika, 2025)
WeTV is one of the video on demand streaming services, or what is usually called a video streaming application service provider based on applications and websites. Several problems have occurred with the WeTV application. Such as applications that are incomplete / lack updates to the content provided, user complaints that cannot be resolved by WeTV, and applications that suddenly error. Therefore, the application was analysed using the E-servqual, IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index) methods. The main objective of this research is to assess the level of user satisfaction with the WeTV application and identify areas that need improvement. Based on the test results using E-servqual, the attributes tested are Efficiency, Responsiveness, Compensation, Fulfillment, System Availability, Privacy and Contact, the results show that the overall expectation value is higher than the perception value (reality) and the Q ≤ 1 value is 0.68. In the IPA method, a cartesian diagram is obtained in each quadrant. The results on CSI get a value of 64.21% with a fairly satisfied category. Therefore, the application does not meet the standards or cannot be said to be good because it does not meet the standards of user expectations